The Effect of Reflux Time from Natural Zeolite on Electrical Conductivity - Fadli M; Gusnedi Gusnedi; Ratnawulan Ratnawulan; Riri Jonuarti (Department of Physics, Universitas Negeri Padang, 2023)
This study aims to determine the electrical properties, namely the value of the electrical conductivity of natural zeolite. Natural zeolite was synthesized using the reflux method with NaOH as an activator with variations of 12, 24, and 36 hours with a molar concentration of 5 M NaOH. Tests were carried out using XRF characterization (X Ray fluorescence), XRD (X Ray Diffraction), and LCR Meter. The XRD results showed the highest peak value at 36 hours of 85.22 nm. The XRF results of the zeolite elements formed were 66.087% SiO2 and 8.45% Al2O3. And in the LCR Meter test, the highest conductivity value was obtained at 36 hours of reflux with a conductivity value of 5.5x10-2 S/m. The value of the electrical conductivity is directly proportional to the particle size where the greater the conductivity value the greater the particle size produced.The electrical conductivity results showed that zeolites are included in semiconductor materials and have the potential as supercapacitor electrodes